Depositional Setting and Quaternary Stratigraphy of the Sheepscot Estuary, Maine: A Preliminary Report - Belknap, Daniel; Shipp, R.; Kelley, Joseph (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTThe Sheepscot River estuary in west-central coastal Maine is a typical example of a long linear embayment sculpted by glacial ice flowing nearly parallel to bedrock strike. After initial déglaciation 13,500 yrs. BP it was covered by glaciomarine mud, the Presumpscot Formation. Isostatic rebound resulted in a rapid sea-level fall and the channeling, winnowing, and consolidation of the Presumpscot Formation, until sea-level reached a lowstand about 65 m below present, 9500 yrs. BP. Subsequent sea-level rise caused flooding of the paleovalley of the Sheepscot, with reworking of the Pleistocene. High resolution seismic reflection profiling, vibracoring, and surficial mapping has allowed reconstruction of the Quaternary stratigraphy and the generation of an evolutionary model of sedimentary environments. At present the estuary exhibits three zones : an outer zone stripped of sediment, a middle zone undergoing erosion by tidal currents and slumping on bluffs and channel margins, and an inner zone of sediment accumulation on flats and in marshes, with redistribution of sediments by tidal currents. This three-fold division held throughout the Holocene transgression, with sediments being temporarily stored in the upper regions of the estuary, and reworked as sea-level rise continued.